Technological Parameters and PMMA Surface Structure - Sykorova, Libuse; Knedlova, Jana; Pata, Vladimir; Kubisova, Milena (Manufacturing Technology Journal, 2018)
The paper focuses on the issue of microprocessing of polymer materials by laser. Specifically, the task is solved by changing the technological parameters, namely the cutting speed, the power and a change of DPI and their impact on the resulting surface quality and depth of cut. During machining, the input technological parameters were changed and followed by evaluation of their interaction with the concentrated radiant energy of the laser beam PMMA, as and representative of the amorphous polymers, was selected for experimental machining. It is one of the best machinable polymer materials regarding this unconventional technology, and it is also frequently applied in industrial practice.
Keywords: Laser beam; Laser Mode; Technological Parameters. Amorphous Polymers